Pengembangan Sistem Manajemen Barang Inventaris SMKN 1 Pasuruan Berbasis Website Menggunakan Metode Rapid Application Development - Muhammad Dzulhilmi Rifqi Bassya; Faizatul Amalia; Sigit Adinugroho (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Inventory is one of the important things for institutions to support various kinds of needs. One of the institutions that cannot be separated from inventory is schools. There are so many items in school that it is necessary to have better inventory management to manage these items so that these items can be used properly. However, this can cause various problems if management is still conventional, data items can be lost, damaged, and mismatch data between one data and another. Therefore, an inventory management system was created so that can use make it easier to manage inventory. System is built in website platform using ReactJs and Redux, and programming language is javascript, html, and css. Database system using firebase. System development life cycle using RAD (Rapid Application Development), this methodology has been choosen because the design work process involves the user, so the results obtained are in accordance with the users hope. Functional testing in this research uses whitebox testing and blackbox testing. Non-functional testing uses compatibility testing and security testing. The results of functional testing using blackbox and whitebox testing are 100% valid and the results of non-functional testing which is security testing is 100% valid while the results of compatibility testing are only be run on certain versions of the browsers.